ROLE OF VITAMIN E IN GROWTH OF AN INDIAN MAJOR CARP, CATLA (CATLA CATLA) - SINHA, Y.K.P.; SINHA, ARCHANA (Journal of Indian Fisheries Association, 2015)
A feeding trial was conducted to study the role of vitamin E in growth of Catla catla fry. Newly hatched larvae of Catla were fed with synthetic diet, supplemented with ’graded levels of vitamin E @ 0,50,100,150,200,250 mg per Kg of diet. The spawn were fed with five times of their body weight for 30 days. Observation were made on the basis of survival, growth, daily weight gain and food conversion ratio. The significant weight gain and highest survival could be achieved by the diet supplemented with 150 mg of vitamin E per kg of the diet. The weight gain per day in 0, 50, 100, 150, 200 and 250 mg vitamin E/kg supplemented diet were 4.0, 5.2, 6.5, 7 .8, 6.8, and 6.3 mg, while survival was 50, 51.8, 52.4, 52.8, 52.2, and 52% respectively.